Stability control of electric vehicles with in-wheel motors by considering tire slip energy. (1st March 2019) - Zhao, Bin; Xu, Nan; Chen, Hong; Guo, Konghui; Huang, Yanjun
Highlights: A hierarchical control framework and an adapted distribution method was proposed. A new semi-empirical tire slip energy model with higher precision is developed. The vehicle stability and minimizing tire slip energy are integrated in torque distribution. The proposed controller and distribution methods saves up to 16.62% tire slip energy. Abstract: Tire wear and overuse are serious issues for four-in-wheel-motor-driven electric vehicles (FIWMD EVs). As a result, this paper proposes a hierarchical control framework to improve the safety of FIWMD EVs while save the tire slip energy (i.e. reduce the tire wear), which includes a linear quadratic regulator (LQR) in the outer layer and a holistic corner controller (HCC) in the inner layer. The LQR can highly improve the lateral stability of the vehicles under extreme conditions by producing an additional yaw moment and a front wheel steering angle. Whereas, the HCC can efficiently distribute the deviation of the longitudinal force and the additional yaw moment by a step-ahead prediction. In this framework, to reduce the tire slip energy, a semi-empirical tire slip energy model is developed and used for tuning the HCC controller. In this way, not only the lateral stability of such EVs can be ensured but also the tire slip energy can be reduced. More importantly, this paper compares the lateral stability and slip energy of the vehicle under lane change condition between four methods – without control, traditional axis distribution, tire workload usage and tire slip energy. The results demonstrate that the proposed controller presents an excellent control capability. In addition, different from the widely used axis load distribution, the longitudinal velocity of the proposed method is more stable. More importantly, the tire slip power and energy are much smaller than others. It achieves 16.62% reduction of the tire slip energy.